Pengaruh substitusi tepung tempe edamame (Glycine max (L.) Merrill) terhadap tekstur dan warna crackers - Difaa' Millati 'Izzah; Aan Sofyan (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2026)
Indonesia has a high potential for edamame production, so it needs to be developed into value-added food products, one of which is through the use of edamame tempeh flour as a substitute for wheat flour in crackers. Edamame tempeh flour contains quite high protein and fiber, so it has the potential to increase the nutritional value of the product without reducing its physical characteristics. In addition, the use of edamame tempeh flour can be an alternative for diversification of legume-based foods that have a long shelf life and are easily applied in various product formulations. This study aims to determine the effect of edamame tempeh flour substitution (0%, 5%, and 15%) on the texture and color of crackers. The study used a Completely Randomized Design (CRD) with three treatments including one control and two replications each. Crackers were made according to the standard formulation, then their texture was analyzed using an AMETEK TA1 Texture Analyzer to obtain hardness, fracture, crispiness, and crunchiness values. Color was analyzed using a CR-400 Colorimeter with L*, a*, and b* parameters. Data were tested using One Way ANOVA. The results showed that the substitution of edamame tempeh flour significantly affected the crunchiness parameter (p<0.05), but did not affect hardness, fracture, crispiness, L*, a*, and b* (p>0.05). Crunchiness decreased with increasing substitution of edamame tempeh flour, while other textures tended to be stable. The color parameter also did not show significant differences between treatments so that the addition of tempeh flour was not able to affect the L*, a*, and b* values of the product.